Morfologi Biji Indigofera sebagai Karakter Penciri dalam Studi Taksonomi - Muzzazinah, Muzzazinah (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
Characteristics of seeds such as seed shape, color, size, texture of the seed coats and hilum shape can be used to solve classification problems. With biology microskop observations obtained under specification of character seeds for 12 species of Indigofera from Indonesia and Saudi Arabia. The results showed that the pattern of seed coat ornamentation, hilum, seed shape may help in the identification of the species..